2014
DOI: 10.1007/s00726-014-1700-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary hepatocytes from mice lacking cysteine dioxygenase show increased cysteine concentrations and higher rates of metabolism of cysteine to hydrogen sulfide and thiosulfate

Abstract: The oxidation of cysteine in mammalian cells occurs by two routes: a highly regulated direct oxidation pathway in which the first step is catalyzed by cysteine dioxygenase (CDO) and by desulfhydration-oxidation pathways in which the sulfur is released in a reduced oxidation state. To assess the effect of a lack of CDO on production of hydrogen sulfide (H2S) and thiosulfate (an intermediate in the oxidation of H2S to sulfate) and to explore the roles of both cystathionine γ-lyase (CTH) and cystathionine β-synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 55 publications
(93 reference statements)
3
29
0
Order By: Relevance
“…Liver thiosulfate was elevated in Cdo1 –/– mice, being 2.2–3.2 times the values for wild‐type controls. Elevated thiosulfate levels in Cdo1 –/– mice have been reported previously and are related to the excess flux of cysteine through desulfhydration pathways in the Cdo1 –/– mouse.…”
Section: Resultssupporting
confidence: 66%
“…Liver thiosulfate was elevated in Cdo1 –/– mice, being 2.2–3.2 times the values for wild‐type controls. Elevated thiosulfate levels in Cdo1 –/– mice have been reported previously and are related to the excess flux of cysteine through desulfhydration pathways in the Cdo1 –/– mouse.…”
Section: Resultssupporting
confidence: 66%
“…Also reported in the CDO KO mice is an increase in the urinary excretion of thiosulfate, coupled with higher tissue and serum cystathionine and lanthionine levels. Importantly, the inhibition and destabilization of cytochrome c oxidase are observed that again is consistent with increased production of H 2 S [249, 250]. Thus, it would appear that the ability of CDO to control cysteine levels may be necessary to maintain low H 2 S/sulfane sulfur pools within tissues to facilitate the use of H 2 S as a signalling molecule [251].…”
Section: Cysteine Dioxygenase Knockout Mouse Modelsmentioning
confidence: 99%
“…However, despite the proposed central role of cysteine dioxygenase in cysteine homeostasis, a knockout of cysteine dioxygenase in mice surprisingly led to only a small increase in intracellular cysteine concentrations. Here, in the absence of cysteine dioxygenease, the non-oxidative desulfuration pathway was hypothesized to play a role in cysteine detoxification 22. Collectively, these data suggest the existence of other mechanisms to handle cysteine overload, which remain uninvestigated.…”
Section: Introductionmentioning
confidence: 95%